MODEL PEMBELAJARAN TOLERANSI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 35 JAKARTA - Muzaeni, Akhmad; Susanto, Susanto; Agus, Agus (PMPP Lembaga Penelitian dan Studi Kebijakan, 2024)
This research aims to determine the Model of Teaching Tolerance in Islamic Religious Education Subjects at SMK 35 Jakarta which includes Learning Models, Tolerance, Islamic Religious Education Subjects, Learning Models, Types of Tolerance, What is the Meaning of Islamic Religious Education. Through research using qualitative methods, with a case study design approach. To explore data using observation, interviews and documentation. Next, the results of these techniques are selected according to the research focus. The results found in this research are a form of application of the Tolerance Cultivation Model in Islamic Religious Education Subjects at SMK 35 Jakarta. It is absolutely mandatory to implement tolerance at SMK 35 Jakarta, because material about tolerance is discussed in Islamic religious subjects. The model of developing tolerance in Islamic Religious Education subjects is an approach that aims to shape the character of students who are able to appreciate, respect and practice tolerance between religious communities. This model was developed with the aim of strengthening understanding of religious tolerance in the Islamic context. In this model, the learning approach used is to study Islamic principles which are the basis for tolerance. Students will learn the teachings of the Islamic religion which upholds love, mutual respect and respect for differences in the school. The method used in this model is a combination of students, teacher educators, and independent research. The expected result of this model is that students have a better understanding of the values of tolerance in the Islamic religion. They are expected to be able to apply and carry out the principles of tolerance in their daily lives, both within the school environment and in the wider community. Apart from that, this model is also expected to increase students' understanding and positive attitudes towards people of other religions, thereby creating an atmosphere of harmony and harmony in religious life in society